2019
DOI: 10.1038/s41401-019-0324-7
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderic acid hinders renal fibrosis via suppressing the TGF-β/Smad and MAPK signaling pathways

Abstract: Renal fibrosis is considered as the pathway of almost all kinds of chronic kidney diseases (CKD) to the end stage of renal diseases (ESRD). Ganoderic acid (GA) is a group of lanostane triterpenes isolated from Ganoderma lucidum , which has shown a variety of pharmacological activities. In this study we investigated whether GA exerted antirenal fibrosis effect in a unilateral ureteral obstruction (UUO) mouse model. After UUO surgery, the mice were treated with GA (3.125, 12.5, and 50 mg· … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(76 citation statements)
references
References 55 publications
4
70
0
Order By: Relevance
“…αSMA plays key roles in epithelial-mesenchymal transition (EMT). [34][35][36] In this study, the findings indicated that HGF can inactivate αSMA. Emodin significantly enhanced the suppressive effect of HGF on this protein.…”
Section: Discussionsupporting
confidence: 52%
“…αSMA plays key roles in epithelial-mesenchymal transition (EMT). [34][35][36] In this study, the findings indicated that HGF can inactivate αSMA. Emodin significantly enhanced the suppressive effect of HGF on this protein.…”
Section: Discussionsupporting
confidence: 52%
“…Our immunoblot analysis revealed decreased expression levels of MMP‐2 and MMP‐9 in UGDH‐silenced ovarian cancer cells, which is consistent with previous reports. There is growing evidence that the ERK/MAPK pathway participates in the regulation of EMT‐related factors such as E‐cadherin, vimentin, SNAIL, SIP‐1 and TWIST 47‐49 . Our data demonstrated that UGDH overexpressing TOV21G HI cells express higher levels of phosphorylated‐ERK, MMP‐2, SIP‐1 and SNAIL, whereas knockdown of UGDH leads to decreases in these markers, indicating that UGDH is involved in regulating ERK, MMP‐2 and EMT markers in ovarian cancer.…”
Section: Discussionmentioning
confidence: 57%
“…There is growing evidence that the ERK/ MAPK pathway participates in the regulation of EMT-related factors such as E-cadherin, vimentin, SNAIL, SIP-1 and TWIST. [47][48][49] Our data demonstrated that UGDH overexpressing TOV21G HI cells express higher levels of phosphorylated-ERK, MMP-2, SIP-1 and SNAIL, whereas knockdown of UGDH leads to decreases in these markers, indicating that UGDH is involved in regulating ERK, MMP-2 and EMT markers in ovarian cancer. We also revealed that knockdown of UGDH inhibits EMT, possibly through the ERK/MAPK pathway (Figure 7).…”
Section: Control Shugdhmentioning
confidence: 64%
“…Studies have found that EMT is of profound significance in fibrosis and pervasive in different organs, such as the lungs, lens, liver, and kidney (Liang et al, 2014 ; Kong et al, 2015 ; Yang et al, 2019 ; Yao et al, 2019 ). Furthermore, EMT has been observed to improve the onset of kidney fibrosis, and fibrotic damages could be alleviated by repressing the process of EMT (Du et al, 2012 ; Geng et al, 2019 ). Clinical studies have suggested that EMT, as the early onset element of interstitial fibrosis in the kidney, is confirmed in diabetic patients (Hills and Squires, 2011 ; Carew et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%